Geochemical and microbiological controls on the transport of Uranium through soil - Stone, Dorothy Grace (Cranfield University, 2009)
Widespread use of depleted uranium (DU) in munitions around the world has raised questions about contamination of soils, water and vegetation with uranium (U). However, understanding of processes controlling the fate and behaviour of U in soils is poor. The aim of this research was to investigate the contributions of abiotic and biotic processes to U transport in soils, by measuring transport in well-controlled experimental systems, and comparing the results with predictions of models of solute transport and reaction. Investigating the role of abiotic processes is challenging due to the complex speciation chemistry of U in soil solutions, sorption reactions with soil surfaces, and the kinetics of local equilibration with soil particles. To simplify the system, the self- diffusion of 235 U against 238 U isotopes was considered, such that speciation and sorption environments were constant. Rates of self-diffusion of these isotopes were measured in four contrasting soils, together with the components of the soil U diffusion coefficient. The results showed that U diffusion was controlled by sorption processes in all the soils, and that slow local-equilibration processes had a major effect. The concentration-distance profiles of U in the soils could not be explained with a simple model assuming instantaneous solid:solution equilibration, and some U spread far further than predicted for equilibrium sorption. Differences in U sorption between the soils were not simply related to differences in soil pH, clay content, CEC or mineralogy. To investigate biotic effects, rates of bulk diffusion of U were measured in sterilised soil, and soil in which prokaryotes or eukaryotes were inhibited by biocides. Slow local-equilibration processes were again found to affect diffusion, but transport was also somewhat increased by biotic processes, hypothesised to be due to differences in CO2 pressure arising from microbial activity and thereby U speciation. This has implications for the effects of perturbation on rates of U transport through soil.